Analisis Nilai Religius dalam Novel Merindu Baginda Nabi Karya Habiburrahman El Shirazy dan Pemanfaatannya sebagai Bahan Ajar - Saraswati, Saraswati (Jurnal Artikula, 2021)
This research is entitled Analysis of Religious Values in the Novel Merindu Baginda Nabi by Habiburrahman El Shirazy and Its Use as Teaching Materials in Schools. The background of the problem in this study is to determine and describe the religious values in the novel Merindu Baginda Nabi by Habiburrahman El Shirazy, and their use as teaching materials in schools. The aim of the researcher is to describe religious values and their use as teaching materials in schools by describing (1) aspects of religious values, including (a) human relations with God, (b) human relationships with humans, (c) human relationships with oneself (d) ) human relations with the natural surroundings (2) its use as teaching materials in schools. The method used in this study is a qualitative descriptive method, the method used is a reading and note-taking technique, while the source of data used in this study is a novel entitled Merindu Baginda Nabi by Habiburrahman. for students in analyzing religious values and moral values in the novel Merindu Baginda Nabi by Habiburrahman El Shirazy, (2) For readers of literary works, especially novels, should be able to understand the values contained in the novel, especially religious values (3) For other researchers, this study it is recommended that it can provide motivation, information, and can be used as reference material for conducting research on literary works, especially novels in other broader and deeper aspects, (4) For Indonesian language teachers, this research is expected to be useful as a comparison to teaching literature , enrich insight , and is expected to be a reference in using learning media, namely the novel Merindu Baginda Nabi by Habiburrahman EL Shirazy.